Methylene blue for vasoplegic syndrome treatment in heart surgery: fifteen years of questions, answers, doubts and certainties - Evora,Paulo Roberto Barbosa (2009)
OBJECTIVE: There is strong evidence that methylene blue (MB), an inhibitor of guanylate cyclase, is an excellent therapeutic option for vasoplegic syndrome (VS) treatment in heart surgery. The aim of this article is to review the MB's therapeutic function in the vasoplegic syndrome treatment. METHODS: Fifteen years of literature review. RESULTS: 1) Heparin and ACE inhibitors are risk factors; 2) In the recommended doses it is safe (the lethal dose is 40 mg/kg); 3) The use of MB does not cause endothelial dysfunction; 4) The MB effect appears in cases of nitric oxide (NO) up-regulation; 5) MB is not a vasoconstrictor, by blocking of the GMPc system it releases the AMPc system, facilitating the norepinephrine vasoconstrictor effect; 6) The most used dosage is 2 mg/kg as IV bolus followed by the same continuous infusion because plasmatic concentrations strongly decays in the first 40 minutes; 7) There is a possible "window of opportunity" for the MB's effectiveness. CONCLUSIONS: Although there are no definitive multicentric studies, the MB used to treat heart surgery VS, at the present time, is the best, safest and cheapest option, being a Brazilian contribution for the heart surgery